DEVELOPMENT OF REACTIVE ULTRAFINE TREATED RICE HUSK ASH (UFTRHA) IN ENHANCING STRENGTH AND DURABILITY PROPERTIES IN CEMENT PASTE - SAAD, SITI ASMAHANI (2018)
Indeed, it is proven that rice husk ash (RHA) contains high amount of amorphous silica that is essential in concrete strength development. Despite of many research of regarding conventional RHA since 1970’s, usage of conventional RHA is still unfavourable in current concrete industry. The principal aim of this research was to improve the RHA properties by introducing thermochemical pretreatment process prior to burning procedure of raw rice husk (RH) at a relatively low acid concentration